Pengaruh Motivasi dan Self-Efficacy dalam Pembelajaran Berbasis Proyek - Wilyati Agustina Bangun; Tria Muhamad Aris (IKIP Budi Utomo Malang, 2022)
This study aims to determine the effect of project-based learning on student motivation and self-efficacy. Project-based learning is a learning technique that has proven effective because it allows students to take an active role in their own learning process. By participating in a project-based learning model, students can build their own knowledge and reflect on their learning projects, resulting in increased motivation and self-efficacy. In this particular study, 80 students . The project in this research is a video production that requires students to work collaboratively. The results of this study support the idea that project-based learning has a positive influence on student motivation and is able to improve collaborative skills.